PVT-independent dB-linear reconfigured local-feedback digital variable gain amplifier. (April 2016) - Lee, Tzung-Je; Hsiao, Wei-Chih
Abstract: This paper proposes a PVT (process, voltage, temperature)-independent dB-linear digital VGA (variable gain amplifier) using reconfigured local-feedback transconductance stages. By using the local-feedback stage, the transconductance is independent to the input voltage. With the reconfigured topology, the linearity in decibel of the voltage gain is improved. Moreover, the voltage gain is independent to PVT variations. Based on the post-layout simulation, the worst absolute value of the gain error is 0.33 LSB at the corner of [FF, 75 °C]. The gain error is measured to be 0.32 LSB with dynamic gain range of 40.76 dB (−23.58 to 17.18 dB). When the frequency of the input signal is 20 MHz and the control word is 0000, the P 1 dB and the NF are 21.14 dBm and 0.048 dB, respectively. The proposed design is implemented by using a typical 0.18 μm CMOS process. The core area of the proposed design is 0.838×0.838 mm 2 . The power consumption is measured to be 10.25 mW for a 20 pF capacitive load at 20 MHz.